Characterization of Musclin as a New Target for Treatment of Hypertension. (9th March 2014) - Lin, Jia-Wei; Tsai, Cheng-Chia; Chen, Li-Jen; Niu, Ho-Shan; Chang, Chen Kuei; Niu, Chiang-Shan
Abstract : Musclin is a novel skeletal muscle-derived factor found in the signal sequence trap of mouse skeletal muscle cDNAs. Recently, it has been demonstrated that musclin is involved in the pathogenesis of spontaneously hypertensive rats (SHRs). However, it is known as a genetic hypertension model. In the present study, we aim to investigate the role of musclin in another animal model of hypertension and characterize the direct effect of musclin on vascular contraction. The results show that expression of musclin was increased in arterial tissues isolated from DOCA-salt induced hypertensive rats or the normal rats received repeated vasoconstriction with phenylephrine. Additionally, direct incubation with phenylephrine did not modify the expression of musclin in the in vitro studies. Also, the direct effect of musclin on the increase of intracellular calcium was observed in a concentration-dependent manner. These results provide the evidence to support that musclin is involved in hypertension. Thus, musclin is suitable to be considered as a novel target for treatment of hypertension.